Legal Study of the Legality of the Palm Oil Rejuvenation Program Regarding the Completeness and Correctness of the Proposal Documents Regulated by Ministerial Regulation No. 19 Of 2023 Amendment to Ministerial Regulation No. 3 Of 2022 - Antonio, Hans Ivander; Pakpahan, Kartina; Isnainul, OK (International Journal of Business, Law, and Education, 2024)
The government, especially the Minister of Agriculture, through the Regulation of the Minister of Agriculture No. 19 of 2023 concerning amendments to the Regulation of the Minister of Agriculture No. 3 of 2022 concerning Human Resource Development, Research and Development, Rejuvenation, and Facilities and Infrastructure for Oil Palm Plantations to ensure the development of sustainable oil palm plantations, has made regulations regarding the development of human resources, research and development, rejuvenation, and facilities and infrastructure for oil palm plantations funded by funds collected from oil palm plantations. The research uses a normative juridical approach with secondary data analysis from written and electronic sources. The results of this study The government must further socialize the regulations on fulfilling the completeness of documents related to the mechanism for rejuvenating oil palm for farmers whose situations and conditions experience difficulties in fulfilling the requirements for rejuvenating oil palm with government assistance. If the completeness of the applicant's documents cannot be fulfilled by the applicant, the applicant will be given an opportunity by the head of the district/city service as stated in Article 25 paragraph (1) letter (b) of the Regulation of the Minister of Agriculture Number 19 of 2023. The solution provided by the government in this case the Ministry of Agriculture for applicants in completing and verifying the validity of the applicant's documents has been stated in Article 17 paragraphs (3) to (5) of the Regulation of the Minister of Agriculture No. 19 of 2023 by providing time for applicants to complete the problem of ownership documents as one of the main requirements for submitting the application for rejuvenation of oil palm.